OPTIMIZATION OF BIOLOGY LEARNING MEDIA IN IMPROVING LEARNING EFFECTIVENESS BASED ON STUDENTS’ LEARNING STYLES - Hughes Bazura (LPPM Universitas Islam Darul `Ulum Lamongan, 2025)
ABSTRACT This study aims to analyze the optimization of Biology learning media to improve learning effectiveness based on students’ learning styles. The research was conducted at MAN 1 Medan in September 2025 with one Biology teacher as the main respondent, chosen because of active use of various instructional media and adaptation of teaching strategies to student characteristics. Data were collected through a closed-ended questionnaire and semi-structured interviews to explore the types, effectiveness, and compatibility of learning media with students’ visual, auditory, and kinesthetic styles. The findings show that teachers have implemented various media, including visual, digital, and practical tools, to enhance conceptual understanding. Visual media and practicum activities were found most effective, with agreement levels of 95% and 90%, respectively, while limited infrastructure and teachers’ digital competence remain key challenges. The study highlights that optimizing learning media requires adequate facilities, technological skills, and awareness of learning style diversity. Aligning media selection with students’ learning styles increases motivation, engagement, and learning outcomes, supporting the development of adaptive and student-centered Biology learning strategies. Keywords: Biology learning, learning media, learning styles, effectiveness, digital learning